2010
DOI: 10.1038/jhg.2010.17
|View full text |Cite
|
Sign up to set email alerts
|

Family-based association study of IGF1 microsatellites and height, weight, and body mass index

Abstract: Height, weight, and body mass index (BMI) are partly heritable, known to be associated with chronic diseases, and are linked to circulating insulin-like growth factor I (IGF-I) concentrations. IGF-I concentrations are also partly heritable and thus genetic variation at IGF1 could influence height, weight, BMI and the risk of developing chronic diseases. Our objective was to examine the association of genetic variation at IGF1 with height, weight and BMI using a sample of premenopausal women. A familybased stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
3
0
1
Order By: Relevance
“…In addition, after correcting for multiple testing, the current study was unable to find any association between metabolic parameters and several SNPs within the IGF pathway. Again, the current findings may reflect those found in the general population: although IGF polymorphisms were associated in some studies with insulin sensitivity [57,79], Type 1 diabetes [58], fat tissue [55,56] or MetS [51], associations with BMI or weight were not significant in three large studies [59][60]93]. It is therefore possible that there is no true effect of genetic variation in the IGF pathway on metabolic parameters, or only a limited effect.…”
Section: Snp Resultssupporting
confidence: 44%
See 1 more Smart Citation
“…In addition, after correcting for multiple testing, the current study was unable to find any association between metabolic parameters and several SNPs within the IGF pathway. Again, the current findings may reflect those found in the general population: although IGF polymorphisms were associated in some studies with insulin sensitivity [57,79], Type 1 diabetes [58], fat tissue [55,56] or MetS [51], associations with BMI or weight were not significant in three large studies [59][60]93]. It is therefore possible that there is no true effect of genetic variation in the IGF pathway on metabolic parameters, or only a limited effect.…”
Section: Snp Resultssupporting
confidence: 44%
“…Lower concentrations of IGF1 have been associated with higher BMI or the presence of MetS in several general population studies [49][50][51][52], although some studies disagree [53,54]. Similarly, genetic alterations in the IGF pathway have been associated with increased BMI, weight or body composition in the healthy population [55][56][57][58], though some conflicting reports are present [59,60].…”
Section: Introductionmentioning
confidence: 99%
“…An important limitation of this study is that we did not genotype the IGF-1 promoter microsatellite polymorphism, which has been associated with circulating IGF-1 levels [6,10]. However, most previous studies have not observed this polymorphism to be associated with childhood body size.…”
Section: Discussionmentioning
confidence: 99%
“…Further, although genetic variability in IGF-1 and IGFBP-3 has been linked to their circulating levels [5-7], it is unclear whether this same variation may influence childhood body size. Some previous studies of IGF-1 and IGFBP-3 genetic variation in relation to adult height and body size reported associations with a putative functional microsatellite polymorphism [6,8-10], but few studies have examined birthweight [11-13] or childhood body size [14]. Further, the studies that examined birthweight examined only the microsatellite polymorphism associated with adult height in previous studies [11-13].…”
Section: Introductionmentioning
confidence: 99%
“…IGF-1 merangsang neurogenesis (proliferasi/perkembangan sel neuron di otak), dan synaptogenesis (proses pembentukan sinaps baru di dalam otak), dan meningkatkan daya tahan neuron. Selanjutnya berdasarkan penelitian sebelumnya IGF-1 berperan dalam metabolisme glukosa, bekerja sama dengan GH (Growth Hormone) yang memainkan peran utama untuk menginduksi resistensi insulin, dan meningkatkan sistem kekebalan tubuh (system immune) (Fehringer et al, 2010). Secara umum, IGF-1 berperan sebagai mediator peningkatan GH yang mempengaruhi aksi metabolik dan anabolik, sebagai yang mengatur pertumbuhan, diferensiasi, apoptosis, dan transformasi sel (Skottner, 2012).…”
Section: Pembahasanunclassified